2018
DOI: 10.1136/bcr-2018-224457
|View full text |Cite
|
Sign up to set email alerts
|

Combined ACL reconstruction and Segond fracture fixation fails to abolish anterolateral rotatory instability

Abstract: The Segond fracture (SF) is considered pathognomonic of an anterior cruciate ligament (ACL) tear. However, the anatomy of the soft-tissue attachments responsible for the avulsion of SFs has been a cause of controversy. A 31-year-old male patient presented with an injury to his right knee that resulted in ACL tear and a SF. Open SF fixation and arthroscopic ACL reconstruction were performed. The anatomical dissection demonstrated that the avulsion of SFs had occurred because of the tibial attachment of the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…In terms of knee stability outcomes after surgery, no clinically or statistically significant differences were observed between the Segond fracture and no-fracture groups. Although a case report showed residual anterolateral rotatory knee laxity after combined ACL reconstruction and fixation of a Segond fracture, 11 the present systematic review showed no evidence that the presence of a Segond fracture is associated with greater postoperative rotatory knee instability. Our result is in agreement with a study that investigated the value of MRI findings in predicting preoperative knee laxity in patients with ACL tears, which showed that a Segond fracture was not a significant predictor of high-grade Lachman or pivot-shift grades.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In terms of knee stability outcomes after surgery, no clinically or statistically significant differences were observed between the Segond fracture and no-fracture groups. Although a case report showed residual anterolateral rotatory knee laxity after combined ACL reconstruction and fixation of a Segond fracture, 11 the present systematic review showed no evidence that the presence of a Segond fracture is associated with greater postoperative rotatory knee instability. Our result is in agreement with a study that investigated the value of MRI findings in predicting preoperative knee laxity in patients with ACL tears, which showed that a Segond fracture was not a significant predictor of high-grade Lachman or pivot-shift grades.…”
Section: Discussioncontrasting
confidence: 82%
“…7,12,14,19,32,40 Although some studies concurred with this original description, 20,36,40 others reported that a Segond fracture is an avulsion of the ALL. 7,9,11,19 The ALC Consensus Group stated that “multiple structures, including ALL, deep iliotibial band and biceps aponeurosis, attach in the region of the Segond fracture, and that it remains unclear which may be responsible for this lesion.” 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 6,7,23 con rmed that ACL reconstruction combined with external tendon xation of the ALL joint has achieved good clinical results in long-term follow-up and that postoperative patients perform well in terms of clinical function and imaging. Nonetheless, several scholars 24,25 have pointed out that compared with simple ACL reconstruction, ACL reconstruction combined with ALL reconstruction does not show a signi cant advantage in improving residual axial movement and may even lead to an excessive pronation constraint of the knee join. Based on the clinical results, we believe that the ALL injury caused by Segond fracture may affect the stability of the anterolateral structure of the knee joint.…”
Section: Discussionmentioning
confidence: 99%